Upaya Peningkatan Kemampuan Koneksi dan Kemampuan Berpikir Kritis Siswa melalui Pendekatan Differentiated Instruction: Penelitian Tindakan Kelas pada Materi Komplemen Himpunan di Siswa Kelas VII E SMP Negeri 3 Majalengka - Suhana, Nana (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study is to improve critical thinking skills and mathematical connections in learning mathematics. This research is an action research with collaborative implementation between observers and researchers as actors of action. The research step is a reflection of action with the pattern of